Women’s Meaning About The Discourse of Obesity On Instagram - Septiana Dewi Widyastuti; Dra. Taufik Suprihartini, M.Si (Interaksi Online, 2016)
This study discusses about women who are obsessed with body shape. In connection with the previously research data that women turned out to be obsessed with the body shape.One apparatus that that facilitate the formation of the body is instagram and has enough followers, namely @ms_slimming and @ 20FIT. Instagram is trying to hegemony the reader in accordance with what is being offered that today all of women should pay attention to body shape and weight to make them look attractive. Therefore the purpose of this study is to describe women’s meaning about the discourse of obesity on instagram.This interpretation process includes the contents of the text to see the dominant meaning through preferred reading using semiotic analusis, interpretation of the meaning of the category to see audience in the dominant response, negotiation, or the opposition. The results of the in-depth interviewshows the body weight of women do not close their desire to discipline their body, even though they are in the category of normal weight and underweight, theyalways feel their body is not ideal, it relates to the view by Foucault's Panopticon, it continue to remind the ideals against his body as though supervised, male gaze by mulvey relates to men’s view about female’s body shape, then women feel supervised and then appear an apparatus that facilitates the formation of the body like instagram so a variety of efforts to discipline the body must be done. When the informant saw the ad, women in the category of underweight in a dominant position choose to train their body with trainer and technology use to discipline the body, in a negotiated position tends to pick herbs, in a opposition against the use of slimming cream to discipline the body. Women in the category of normal weight in a dominant position mostly choose to train their body with trainer and technology use as well as herbal to discipline his body, in a negotiated position tend to choose a planking movement, in a opposition against the use of slimming cream to discipline the body. Women in the category of overweight in a dominant position choose herbs to discipline the body, in a negotiated position tend to choose a corset to shape the body, in a position against to form a sexy body with exercise. Women in the category of obese in a dominant position choose to train their body with trainer and technology use to discipline the body, in a negotiated position tend to choose the use of slimming cream, in a opposition against the use of corset and perform a planking movement to discipline the body.